Rainfall interception, throughfall and stemflow in a secondary forest - Nik Ab. Majid, Nik Muhamad; Hamzah, Mohd Basri; Ahmad, Shaharuddin (Universiti Pertanian Malaysia, 1979)
The presence of forest or any other vegetative cover over an area of land influences the distribution pattern of rainfall. Some of the rain is intercepted and retained by the leaves and other parts of the trees and eventually lost to the atmosphere in the form of evaporation. The rain water that reaches the soil surface will arrive there by throughfall (passes directly through open spaces not covered by foliage or as drips from the vegetative parts of the tree) and also by stemflow (flows down the surface of the stem). Measurements of the amount of interception, throughfall and stemflow are therefore necessary towards understanding the role of a forest cover in the hydrological cycle in a forest ecosystem. Studies of rain interception, throughfall and stemflow have received little attention in Malaysia. Kenworthy (1970) reported one such study under primary and disturbed forests at Ulu Gombak Reserve. Teoh(1971) conducted a similar study in a rubber plantation at Sungei Buloh and Low (1972) reported the work done at Sungai Lui catchment area. This paper describes the results obtained from an investigation conducted at the Air Hitam Forest Reserve, Puchong, Selangor to find out the percent interception, throughfall and stemflow. The vegetation is typically a secondary lowland dipterocarp forest of the"Kedondong Kempas" type. An attempt was also made to relate crown area and diameter of trees at breast height (D.B.H.) to stemflow.